2022-RA-1067-ESGO Is laparoscopic radical hysterectomy safe in cervical cancer with tumor size ≤2 cm, even if parametrial invasion or lymph node metastasis is found after surgery?. (20th October 2022) - Kim, Junhwan; Lee, Seoyoon; Kim, Se Ik; Suh, Dong Hoon; Kim, Yong Beom; Kim, Jae-Weon; Choi, Chel Hun; Lee, Maria
Abstract : Introduction/Background: Previously, our research team suggested patients with 2009 FIGO stage IB1 cervical cancer with tumor size ≤2 cm on preoperative magnetic resonance imaging (MRI) were safe candidates as laparoscopic radical hysterectomy (RH) did not influence disease recurrence in this subgroup. We aimed to investigate whether laparoscopic RH is also feasible in parametrial-positive or node-positive, early cervical cancer with a small sized tumor. Methodology: From Cervical Cancer cohorts of three tertiary institutional hospitals, we identified patients with 2009 FIGO stage IB1 who received either open or laparoscopic Type C RH. Among them, those with cervical tumor ≤2 cm on pre-operative MRI and were adherent to the guidelines for adjuvant treatment were included. Patients' clinicopathologic characteristics and survival outcomes were compared between the laparoscopic and open RH groups. Subgroup analyses were conducted according to the presence or absence of parametrial invasion (PMI) and lymph node metastasis (LNM). Results: In total, 498 patients were included: 299 and 199 for laparoscopic and open RH groups, respectively. After surgery, all study population was managed properly in terms of adjuvant treatment. After a median observation period of 59.4 months, the two groups showed similar progression-free survival (PFS; P=0.615) and overall survival (P=0.439). On pathologic examination, 16 (3.2%) and 49 (9.8%) had PMI and LNM, respectively, and 10 (2.0%) had both. In a subgroup of PMI, no difference in PFS was observed between the laparoscopic and open RH groups (P=0.893). In a subgroup of LNM, the two groups also showed similar PFS (P=0.169). Consistent results were also found in subgroups of non-PMI and non-LNM. Conclusion: Our study results demonstrate that laparoscopic RH might be safe in early cervical cancer with tumor size ≤2 cm, regardless of parametrial and nodal status, when adjuvant treatment is administered properly. Further large cohort studies are warranted to support our findings.